The Correlation between Students Perception of Learning Environment and Self Directed Learning Readiness in The Faculty of Medicine Sebelas Maret University - Alifa Rizka Apriliananda; Arsita Eka Prasetyawati; Ari Natalia Probandari (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Learning environment is everything that happened in the class, departement, faculty or university that plays a very important role in effective student learning. Students perception of the learning environment is also found to influence their behaviour. Student participation in problem-based learning (PBL) curricula leads to use of Self Directed Learning (SDL) skills. SDL, which is a prerequisite for life-long learning can flourishin certain learning environments. This study aimed to investigate the relationship between students perception of learning environment and self directed learning readiness in the Faculty of Medicine Sebelas Maret Universtity. Method: This study was an observational analytic study with cross sectional method approach among 106 medical students of Sebelas Maret University that selected by Systematic Random Sampling method. This research used DREEM (Dundee Ready Educational Environment Measure) that measured the students perception of learning environment and SDLRS that measured students self directed learning readiness. Data analysis used Pearson correlation (? = 0.05). Result: Pearson correlation test results a significant correlation between Students Perception of Learning Environment with Self Directed Learning Readiness in The Faculty of Medicine Sebelas Maret University with p <0.05 (p = 0.000). The test results also showed a moderate correlation between two variables with a correlation coefficient (r) 0.551, with increased students perception of learning environment will increase self directed learning readiness in the Faculty of Medicine Sebelas Maret University. Conclusion: There is a moderate relationship between Students Perception of Learning Environment and Self Directed Learning Readiness in The Faculty of Medicine Sebelas Maret University. Better students perception of learning environment, will increase students self directed learning readiness Keywords: learning environment, perception of learning environment, self directed learning readinesss